Nigeria-China Bilateral Trade Relations: Is There Market Opportunities in China? - Ibrahim, Kabiru Hannafi; Sari, Dyah Wulan; Handoyo, Rossanto Dwi (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
This study used normalized revealed sectoral comparative advantage, import demand share, growth identification and facilitation framework to identify market opportunities for Nigeria in the Chinese markets over the period 1988-2017. Our findings revealed that Nigeria has a steady and long-term comparative advantage in few commodities and there is limited scope for Nigeria to improve on its balance of trade due to limited export potentials. Furthermore, sixteen market opportunities were identified, out of which fourteen are stable and growing markets. Our findings also revealed that these market opportunities can't all be meet by Nigeria, as these commodities were not exportable due to poor competitive position and highly capital-intensive nature of the commodities. These findings are not only relevant to academics but also for policy making.